Geburtsfest - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1994)
GEBURTSFEST / FESTIVAL OF BIRTH choir music with sound scenesof MONDAY from LIGHT(Version of EVE'S FIRST BIRTH-GIVING for choir a cappella and tape).......